Upaya Meningkatkan Kemampuan Kognitif Anak Melalui Permainan Tutup Botol Angka di TK Bhakti Pertiwi - Rizky Agustina Wulandari; Rizki Amalia; Melvi Lesmana Alim (Jurnal Pendidikan Tuntas, 2024)
This research was motivated by the low cognitive abilities of children aged 5-6 years at Bhakti Pertiwi Kindergarten, Kampar Regency. For this reason, a concrete application is needed to find the right way to relate to children's cognitive abilities, namely the number bottle cap game. This research aims to find out whether the application of the number bottle cap game can improve cognitive abilities in children aged 5-6 years at TK Bhakti Pertiwi Kampar Regency. This type of research is classroom action research which is an examination of learning activities in the form of actions, which are deliberately created and occur in a class together with a total of 17 children. Data collection techniques for data collection in this research are observation and documentation. The data analysis technique used in this research is the percentage technique. From the results of classroom action research and discussions as described, a conclusion was drawn regarding the results of this research, namely that the implementation of the number bottle cap game activity can improve the cognitive abilities of children aged 5-6 years at TK Bhakti Pertiwi Kampar Regency. The cognition of children aged 5-6 at TK Bhakti Pertiwi Kampar Regency, through the implementation of the number bottle cap game activity, has increased every cycle. In the pre-cycle, an average score of 43.38% was obtained with the BB (Not Yet Developed) criteria. After improvements were made in cycle I, a score of 54.23% was obtained with MB (Starting to Develop) and in cycle II a score of 78.68% was obtained with BSB (Very Well Developing) criteria. Keywords: Number Bottle Cap, Game, Cognitive Child